2016
DOI: 10.3897/compcytogen.v10i1.6407
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome diversity in Armenian toad grasshoppers (Orthoptera, Acridoidea, Pamphagidae)

Abstract: Although previous cytogenetic analysis of Pamphagidae grasshoppers pointed to considerable karyotype uniformity among most of the species in the family, our study of species from Armenia has discovered other, previously unknown karyotypes, differing from the standard for Pamphagidae mainly in having unusual sets of sex chromosomes. Asiotmethis turritus (Fischer von Waldheim, 1833), Paranocaracris rubripes (Fischer von Waldheim, 1846), and Nocaracris cyanipes (Fischer von Waldheim, 1846) were found to have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(43 citation statements)
references
References 22 publications
(26 reference statements)
5
38
0
Order By: Relevance
“…In single cases, clusters of rDNA were revealed in the pericentric heterochromatin of all chromosomes in the set (Jetybayev et al 2012). In contrast to Pyrgomorphidae and Acrididae grasshoppers, multiple localization of rDNA clusters on one chromosome in the Pamphagidae family has been shown (Bugrov et al 2016, Jetybayev et al 2017). Perhaps, the revealed differences in the localization of rDNA in Pyrgomorphidae and Acrididae on the one hand, and Pamphagidae on the other hand, may contain a certain phylogenetic signal.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In single cases, clusters of rDNA were revealed in the pericentric heterochromatin of all chromosomes in the set (Jetybayev et al 2012). In contrast to Pyrgomorphidae and Acrididae grasshoppers, multiple localization of rDNA clusters on one chromosome in the Pamphagidae family has been shown (Bugrov et al 2016, Jetybayev et al 2017). Perhaps, the revealed differences in the localization of rDNA in Pyrgomorphidae and Acrididae on the one hand, and Pamphagidae on the other hand, may contain a certain phylogenetic signal.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, recently, a new model of the Y-chromosome evolution was proposed based on studies in Pamphagidae grasshoppers. It was shown that in Pamphagidae grasshoppers centric fusion of the X chromosome and autosome occurred independently in two phylogenetic branches, and due to further evolution the neo-Y chromosome exhibited different stages of degradation process (Bugrov et al 2016, Jetybayev et al 2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pamphagidae family is one of the few taxa among grasshoppers, which includes phylogenetic lineages characterized by the neo-sex chromosome systems. Recently species of this family were karyotyped and the neo-sex chromosomes were described with C-banding of mitotic and meiotic chromosomes and FISH of 28S rDNA and telomeric repeats [ 23 , 24 , 32 , 33 ]. However, understanding of the neo-sex chromosome evolution requires identification of the autosomes fused with the ancestral X, description of their degradation process and characterization of newly arisen clusters of DNA repeats.…”
Section: Discussionmentioning
confidence: 99%
“…The neo-Y is similar to original autosome according to the size. In the second lineage (Nocarodeini tribe of Pamphaginae subfamily), the neo-sex chromosomes exhibit advanced stages of heteromorphization with significant degradation of the neo-Y [ 23 , 24 ]. This study is devoted to the comparative analysis of the neo-sex chromosomes in both evolutionary lineages in Pamphagidae by the generation of microdissected DNA probes from neo-sex chromosomes or their regions, followed by in situ hybridization with chromosomes of different species of Pamphagidae.…”
Section: Introductionmentioning
confidence: 99%